ANALISIS PENERAPAN IJARAH DAN PERLAKUAN AKUNTANSI BERDASARKAN PSAK 107 PADA PT BPRS HIKMAH WAKILAH KOTA BANDA ACEH - Cut Vhintara; Rahmawaty Rahmawaty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
This study aims to see the application of Ijarah and accounting treatment based on PSAK 107 at PT BPRS Hikmah Wakilah in Banda Aceh City. The research was conducted using qualitative-descriptive research method. The type of data used is qualitative data, that is by way of field study method consisting of, observation, interview, and company documentation. The results of this study indicate that the application of Ijarah and accounting treatment at PT BPRS Hikmah Wakilah Banda Aceh has been in accordance with PSAK 107.